A Planar Graphene‐Based Film Supercapacitor Formed by Liquid–Air Interfacial Assembly. Issue 9 (13th February 2017) - Chen, Xiangrong; Xiang, Ting; Li, Zhengjie; Wu, Yanlin; Wu, Hailong; Cheng, Zhaofa; Shao, Jiao‐Jing; Yang, Quan‐Hong
Abstract : A liquid–air interfacial assembly is used to produce a flexible substrate‐supported graphene film, which does not need the tedious substrate‐transfer procedure that is generally required for many other film‐making methods. The graphene film is used as the active working electrode in its planar configuration and an acidic polymer gel is used as the electrolyte, which leads to a flexible planar graphene film supercapacitor with a large areal specific capacitance of 773 µF cm −2 and superior retention performance. In order to demonstrate the versatile application of interfacial assembly in obtaining graphene‐based hybrid film electrodes, graphene–manganese oxide and graphene–polyaniline hybrid films are assembled and used to construct planar film supercapacitors with areal specific capacitance of 963 and 2561 µF cm −2, respectively. Compared with the graphene film supercapacitor, the graphene–manganese oxide film supercapacitor, with neutral gel electrolyte, shows no apparent increase of specific capacitance, which is probably due to the larger electrolyte ions and hence the slower ion diffusion rate. Overall, the interfacial assembly is a universal technique for the fabrication of flexible, planar graphene‐based film supercapacitors, and this report demonstrates that such supercapacitors are promising as an advanced power system in wearable electronics. Abstract : Graphene films and graphene‐based hybrid films assembled using the liquid–air interfacial assembly can be directly deposited on flexible substrates with no complicated substrate‐transfer procedure and then are used as active electrodes to fabricate the planar film supercapacitors, which have a large areal specific capacitance, excellent capacitive retention, and high flexibility.